Fig tree orchard formation using organic fertilization - Leonel, Sarita [UNESP]; Tecchio, Marco Antonio [UNESP] (My University, 2010)
The present work aimed at evaluating the effects of cattle manure fertilization on the growth and yield of fig trees. The cultivar 'Roxo de Valinhos' was used. One-, two-, three-and four-year-old trees were treated with cattle manure containing 0, 25, 50, 75, 100, 125 and 150% of the recommended nitrogen level per plant. The experiment was carried out using randomized blocks with 7 treatments, 5 replicates and 5 plants per experimental plot. The evaluated characteristics were: plant height, stem diameter, secondary branch length and diameter, yield per plant (kg plant-1), besides some quality characteristics of fruits such as pH, titratable acidity, soluble solids and texture. Manure application enhanced plant growth and fruit production. Significant differences were observed only for soluble solids content, pH and texture, which varied according to the crop cycle. After four crop cycles (2002/03, 2003/04, 2004/05 and 2005/06), the best results (about 5.0 kg of fruits per plant) were obtained with 100% of the recommended nitrogen dose, which corresponded to 14.3 kg of cattle manure per plant, in the last crop cycle (2005/2006).
Keywords: Cattle manure; Ficus carica L.; Yield; Bos; Carica papaya; Ficus (angiosperm); Ficus carica